Relasi Kuasa Dalam Cerpen Kafanu Al - Ustazi Karya Haifa Bitar : Analisis Kuasa Michel Foucault - Nizar, Mohammad; Pujiharto (Philosophiamundi, 2023)
This article attempts to reveal the relations of power, resistance and opposition that exist in the short story "Kafanu Al - Ustazi" in the short story anthology Gurubun wa Kitabah by Haifa Bitar. The theory used in this paper is Michel Foucault's discourse theory which contains relations of power, resistance and opposition. Truth in Foucault's eyes is created because of power which is tied to knowledge. In every power, there is always resistance and opposition to that power. In the analysis, the method used is a qualitative method with a sociological approach which states that literary works are a reflection or abstraction of the real life of a society. Through this approach, we will connect the social reality in the short story "Kafanu Al - Ustazi" with the social reality in Syria at the time when Haifa Bitar wrote the short story. Based on the data analysis, three things were obtained as follows: 1) there is a relations of power in the short story "Kafanu Al - Ustazii" which takes the form of thoughts (knowledge), 2) there is resistance and opposition from the character Aku as the main female character in the short story "Kafanu Al - Ustazi", and 3) the pattern of male domination over women in the short story "Kafanu Al - Ustazi" is a social reality that also occurs in Syria as the background underlying the writing of the short story